1999
DOI: 10.1088/0953-4075/32/8/309
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of the EinsteinA-coefficient used for evaluation of O2(^1Deltag) concentration in the chemical oxygen-iodine laser

Abstract: This paper is a contribution to the current discussion on the Einstein coefficient for spontaneous emission (A-coefficient) of singlet delta oxygen, O2(g), that is often used for an evaluation of O2(g) concentration in a chemical oxygen-iodine laser (COIL). The published values of the A-coefficient vary in a wide range, corresponding to a radiative lifetime of O2(g), , from ~53 to ~151 min. This could make an evaluation of COIL operation questionable. In this paper, the Einstein A-coefficient is estimated, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Because the radiative relaxation time of O 2 (a 1 Δ g ) is 1.24 hours and collisional relaxation becomes less important at higher altitudes, the photochemical interaction thus leads to significantly different variations in O 2 ( 1 Δ) and O 3 at a timescale of a few hours. We have adopted a recent value of 2.24 × 10 −4 s −1 for the Einstein coefficient A z 1 [ Lafferty et al , 1998; Spalek et al , 1999] in the model's standard runs. Our model was also tested with a smaller A z 1 of 1.47 × 10 −4 s −1 used by Mlynczak and Nesbitt [1995] in their sensitivity study, and we found that the peak O 2 (a 1 Δ g ) around 95 km would be increased by about 40% when the smaller value of A z 1 is used in the model, leading to a more significant difference between O 2 ( 1 Δ) and O 3 variations.…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the radiative relaxation time of O 2 (a 1 Δ g ) is 1.24 hours and collisional relaxation becomes less important at higher altitudes, the photochemical interaction thus leads to significantly different variations in O 2 ( 1 Δ) and O 3 at a timescale of a few hours. We have adopted a recent value of 2.24 × 10 −4 s −1 for the Einstein coefficient A z 1 [ Lafferty et al , 1998; Spalek et al , 1999] in the model's standard runs. Our model was also tested with a smaller A z 1 of 1.47 × 10 −4 s −1 used by Mlynczak and Nesbitt [1995] in their sensitivity study, and we found that the peak O 2 (a 1 Δ g ) around 95 km would be increased by about 40% when the smaller value of A z 1 is used in the model, leading to a more significant difference between O 2 ( 1 Δ) and O 3 variations.…”
Section: Model Resultsmentioning
confidence: 99%
“…The photochemical timescales of various species are determined by collisional quenching and radiative relaxation. The relaxation time of the spontaneous emission of O 2 ( 1 Δ) at 1.27 μ m is 1.24 hours [ Lafferty et al , 1998; Spalek et al , 1999]. Therefore, at high altitude where the collisional quenching becomes less important, the photochemical timescale of O 2 ( 1 Δ) could be comparable or longer than the basic timescale and the transport timescale.…”
Section: One‐dimensional Airglow Model and Sensitivity Coefficientsmentioning
confidence: 99%
“…The vertical profile of the a‐X nightglow is determined by the balance between production of O 2 (a) via reaction and its loss due to radiative decay of the O 2 (a) state and collisional quenching. There has been controversy over the lifetime of O 2 (a) against radiative decay, but recent laboratory measurements [ Cheah et al , 2000; Lafferty et al , 1998; Miller et al , 2001; Newman et al , 1999; Spalek et al , 1999] appear to have converged to a consistent value. The mean lifetime we have computed from these studies, 74 ± 3 min is consistent with recent assessments [ Gamache and Goldman , 2001; Slanger and Copeland , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement by Badger et al [1965] of 2.58 × 10 −4 s −1 has been the most widely used value of the Einstein A ‐Coefficient at 1.27 μ m. More recent measurements from laboratory and atmospheric emission studies have ranged from 1.47 × 10 −4 s −1 [ Mlynczak and Nesbitt , 1995] to 2.24 × 10 −4 s −1 [ Lafferty et al , 1998; Špalek et al , 1999]. Pendleton et al [1996] analyzed ground based FTIR measurements of the evening twilight decay of O 2 ( 1 Δ g ) and found a radiative lifetime of about one hour (∼2.8 × 10 −4 s −1 ).…”
Section: Introductionmentioning
confidence: 99%